2014
DOI: 10.1017/s0007114514001779
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of sodium and potassium intakes assessed by two 24 h urine collections in healthy Japanese adults: a nationwide study

Abstract: Excess Na intake and insufficient K intake are well-known risk factors for CVD. International comparative studies have reported that Japan has the highest intake of Na and the lowest intake of K in the world. However, no recent study has precisely assessed Na and K intakes in Japanese adults. In the present study, Na and K intakes were estimated from two 24 h urine collections implemented in twenty-three out of forty-seven prefectures in Japan. Apparently healthy men (n 384) and women (n 376), aged 20 to 69 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 38 publications
5
77
6
Order By: Relevance
“…Although we previously reported that higher BMI was associated with higher Na excretion (i.e. absolute amount of Na intake) (11) , the source of Na in the present study was the same regardless of body constitution. On the other hand, higher BMI was marginally associated with a lower proportion of discretionary Na intake in women on multivariate analysis.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Although we previously reported that higher BMI was associated with higher Na excretion (i.e. absolute amount of Na intake) (11) , the source of Na in the present study was the same regardless of body constitution. On the other hand, higher BMI was marginally associated with a lower proportion of discretionary Na intake in women on multivariate analysis.…”
Section: Discussioncontrasting
confidence: 64%
“…Details of the collection method have been reported elsewhere (11) . One mmol of Na is equal to approximately 58·5 mg of salt (NaCl).…”
Section: Semi-weighed Diet Recordmentioning
confidence: 99%
“…Details of the study have been reported elsewhere. 21 Briefly, 10 dietitians working at 10 different welfare facilities in each of the 20 areas participated as research dietitians. The 20 study areas were selected based on geographical location and the feasibility of recruitment of research dieticians.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the collection method have been reported elsewhere. 21 Briefly, participants set the starting time of collection and then discarded the first urine at the starting time. All subsequent specimens were collected until the same time as the starting time on the next day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation